2019
DOI: 10.1093/gerona/glz165
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Vitamin D and Interleukin 6 on Slow Gait Speed: 6-Year Follow-up Data of Older Adults From InCHIANTI

Abstract: Background Whereas the independent effects of biomarkers, including 25-hydroxy vitamin D (25(OH)D), insulin-like growth factor 1, C-reactive protein, and interleukin 6 (IL-6), on gait speed in older adults have been evaluated, their joint effects on gait speed are not well understood. Methods Study subjects aged at least 65 at baseline (N = 970) were enrolled in the population-based Invecchiare in Chianti (InCHIANTI) study fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Among the few studies that explored this link, findings are mixed. For example, our findings are in line with a study that demonstrated negative associations of CRP and fibrinogen with gait speed in middle-aged women under ST conditions over a 5-year period ( Tomey et al, 2009 ), and with other longitudinal studies, with follow-up of two ( Verghese et al, 2011 ) and 6 years ( Kositsawat et al, 2013 ) that found that IL-6 was negatively related to physical function ( Verghese et al, 2011 ; Kositsawat et al, 2013 , 2020 ; Brown et al, 2016 ). However, in a study of 977 participants aged 65 and above at baseline, no association was observed between CRP levels and physical function measured after three and 6 years ( Kositsawat et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the few studies that explored this link, findings are mixed. For example, our findings are in line with a study that demonstrated negative associations of CRP and fibrinogen with gait speed in middle-aged women under ST conditions over a 5-year period ( Tomey et al, 2009 ), and with other longitudinal studies, with follow-up of two ( Verghese et al, 2011 ) and 6 years ( Kositsawat et al, 2013 ) that found that IL-6 was negatively related to physical function ( Verghese et al, 2011 ; Kositsawat et al, 2013 , 2020 ; Brown et al, 2016 ). However, in a study of 977 participants aged 65 and above at baseline, no association was observed between CRP levels and physical function measured after three and 6 years ( Kositsawat et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, findings from longitudinal studies are somewhat conflicting, with some reporting negative associations between inflammation markers and cognitive function ( Marioni et al, 2009 ; Singh and Newman, 2011 ), but others reporting either none ( Singh and Newman, 2011 ) or limited associations ( Schram et al, 2007 ). As for physical function, the association with inflammation among older adults has been explored ( Cesari et al, 2004 ; Roenneberg et al, 2004 ; Verghese et al, 2011 ; Kuh et al, 2019 ; Kositsawat et al, 2020 ). While most of these studies describe a negative association between inflammation markers and physical function, due to a large heterogeneity between studies (i.e., various inflammation markers and diverse measures of physical performance) generalizability is limited.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study suggested that usage of vitamin D was effective for the prevention of decreased muscle mass [17]. Serum vitamin D level was associated with physical performance and frailty in cross-sectional studies [18,19], and coexisting low serum vitamin D level and high interleukin 6 level were associated with slow gait speed in a cross-sectional study [20]. Vitamin D was reported to suppress muscle atrophy through the suppression of forkhead box protein O1 (FOXO1) in skeletal muscle [16].…”
Section: Introductionmentioning
confidence: 99%
“…Are the cerebrovascular consequences of VDD reversible? Do cerebrovascular and cognitive outcomes correlate in clinical studies investigating the effects of VitD [ 258 , 259 , 260 ]? What is the mechanism underlying the sex-dependence of the cerebrovascular manifestation of VDD?…”
Section: Discussionmentioning
confidence: 99%